2008
DOI: 10.1073/pnas.0709618105
|View full text |Cite
|
Sign up to set email alerts
|

Genomic markers for malignant progression in pulmonary adenocarcinoma with bronchioloalveolar features

Abstract: Bronchioloalveolar carcinoma (BAC), a subtype of lung adenocarcinoma (ADC) without stromal, vascular, or pleural invasion, is considered an in situ tumor with a 100% survival rate. However, the histological criteria for invasion remain controversial. BAC-like areas may accompany otherwise invasive adenocarcinoma, referred to as mixed type adenocarcinoma with BAC features (AWBF). AWBF are considered to evolve from BAC, representing a paradigm for malignant progression in ADC. However, the supporting molecular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…Aviel-Ronen and colleagues (2008) examined genomic changes associated with adenocarcinoma in situ and minimally invasive adenocarcinoma using array comparative genomic hybridization and found that genomic profiles are indistinguishable between adenocarcinoma in situ and minimally invasive adenocarcinoma, although they developed in distinct individuals (5). In contrast, this study successfully revealed that gene expression profiles substantially differed between lepidic growth and microinvasion cancer cells in a single minimally invasive adenocarcinoma.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Aviel-Ronen and colleagues (2008) examined genomic changes associated with adenocarcinoma in situ and minimally invasive adenocarcinoma using array comparative genomic hybridization and found that genomic profiles are indistinguishable between adenocarcinoma in situ and minimally invasive adenocarcinoma, although they developed in distinct individuals (5). In contrast, this study successfully revealed that gene expression profiles substantially differed between lepidic growth and microinvasion cancer cells in a single minimally invasive adenocarcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…The concept of progression from adenocarcinoma in situ to minimally invasive adenocarcinoma is widely accepted (4)(5)(6)(7)(8)(9). Noguchi and colleagues noted 2 types of small (maximum diameter, < 2 cm) adenocarcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…However, a cause-effect relationship is not clear. The gene of ALG-2 (PDCD6, chromosomal locus at 5p15.33) is a potential prognostic marker for malignant progression in pulmonary adenocarcinoma with bronchioloalveolar features, and patients with high expression levels of PDCD6 have low survival rates [70]. By contrast, low expression level of PDCD6 is correlated with poor overall survival of gastric cancer patients [71].…”
Section: Physiological Functions Of Alg-2mentioning
confidence: 98%
“…The role of PDCD6 in cancer development has been explored gradually, but the potential mechanism is still unknown. Previous studies found that PDCD6 is overexpressed in a variety of human tumors (la Cour et al, 2003;Mollerup et al, 2003;Aviel-Ronen et al, 2008;la Cour et al, 2008). However, Mel290 cells derived from a human tumor were found to express lower levels of PDCD6 mRNA and protein than normal melanocytes (Yamada et al, 2008).…”
Section: Zhang Et Almentioning
confidence: 99%
“…Previous research showed that PDCD6-deficient mice develop normally without obvious abnormalities in the immune system ( Jang et al, 2002). Nonetheless, potential physiological roles of PDCD6 in the regulation of ER stress-induced apoptosis (Rao et al, 2004), neuronal cell death during development (Mahul-Mellier et al, 2006), and cancers (la Cour et al, 2003;Mollerup et al, 2003;Subramanian and Polans, 2004;Aviel-Ronen et al, 2008;la Cour et al, 2008;Yamada et al, 2008;Hoj et al, 2009) have been reported.…”
mentioning
confidence: 99%